The Effectiveness of using Quizlet as digital learning to improve vocabulary mastery of junior high school students - Nur, Serliah; Putri, Nurhalisa Eka (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2023)
The aim of this study is to determine the effectiveness of using Quizlet as a digital learning medium to improve the vocabulary mastery of junior high school students. This study applied a quasi-experimental design with pre-test and post-test. The population of this study consisted of the 8th-grade students of MTsN 1 Kota Makassar. Purposive sampling was utilized by the researchers to choose 80 students as a sample and divided them into two classes, experimental and controlled classes. This study used a vocabulary test as the instrument. The vocabulary test was used to determine whether the 'students' vocabulary mastery had improved following the treatment or not. The result of the study shows that there was improvement of 'students' vocabulary after using Quizlet as digital learning media. This is evidenced by the t-test significant value 0.000<0.05, which means that H1 is accepted and H0 is rejected. Therefore, using Quizlet as digital learning media is effective to improve 'students' vocabulary mastery. Quizlet is one of application that can be used as digital learning media with many features that can support the learning process in individuals and groups. Quizlet can also be used in online and offline situations.